Insecticide, Acaricide, Repellent and Antimicrobial Development - Benelli, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present book, a reprint of the Molecules Special Issue "Insecticide, Acaricide, Repellent and Antimicrobial Development", presents key advances in the development of effective and eco-friendly insecticides, acaricides, repellents, and antimicrobials, including products of natural origin.